SATISFACTION OF PATIENTS WITH ARTHROSIS FROM MULTIDISCIPLINARY COOPERATION - Gergana Nenova; Paraskeva Mancheva; Todorka Kostadinova (Peytchinski Publishing, 2016)
INTRODUCTION: The research of patient satisfaction with arthrosis from multidisciplinary cooperation is related to clarifying the position and the role of the physiotherapist in public health and in the development of integrated care. AIM OF THE STUDY: To investigate the satisfaction of patients with arthrosis from multidisciplinary cooperation. MATERIAL AND METHODS: In this research study participated 30 patients of the Department of Orthopedics and Traumatology of University Hospital "St. Marina" EAD - Varna for the period 2012-2016 of which 13 were men and 17 women. A feedback from these patients was sought based on the 5-point Likert scale regarding their satisfaction after the completion of the work of the multidisciplinary task team that provides integrated care at home. The questionnaire includes 12 questions, grouped in the following areas: awareness, attitude / communication, time, physical activity, professionalism and benefit / effectiveness. The data were compared with the results from a study of the satisfaction of a control group of 30 patients who were treated in the same ward, but chose to continue their rehabilitation with NHIF. RESULTS: The respondents from the test group are highly satisfied in the "awareness" area (respectively 4.80 and 4.90). They say that they have more freedom in daily activities after the procedure conducted by physiotherapist (4.93) and would seek the same physiotherapist if they need rehabilitation in the future. Patients appreciate the quality behavior/approach and communication skills displayed by the physiotherapist during the rehabilitation process (5.00), which enables them to better understand their illness (4.93). The respondents from the test group felt much better after each procedure performed by the physiotherapist (5.00) and would recommend him/her to other patients who have the same need (5.00). The satisfaction from the work of the physiotherapist is appreciated by patients extremely high, but only within the model of the multidisciplinary team providing integrated care, in contrast with the very low levels of satisfaction with the quality of rehabilitation provided by the NHIF (control group - 2:43 to issue "8" and 2.40 for question "10"). CONCLUSIONS: the leading role of the physiotherapist is definitely essential for the patient in the model of the integrated care provided by the multidisciplinary task team at home. The health problem is solved by a patient-centered approach in an environment that is familiar and close to him with almost identical costs in terms of money, time, emotions, etc. in comparison with the costs provided by NHIF.